Improved quality of life and pain relief in mature horses with osteoarthritis after oral transmucosal cannabidiol oil administration as part of an analgesic regimen - Interlandi, Claudia; Tabbì, Marco; Di Pietro, Simona; D’Angelo, Fabiola; Costa, Giovanna L.; Arfuso, Francesca; Giudice, Elisabetta; Licata, Patrizia; Macrì, Daniele; Crupi, Rosalia; Gugliandolo, Enrico (Frontiers in Veterinary Science, 2024)
The aim of this study was to evaluate the effect of oral cannabidiol (CBD) administration in addition to a conventional analgesic protocol on the clinical signs of 20 horses with mild joint osteoarthritis. The horses were randomly assigned to either the control group (C group) or the cannabidiol group (CBD group). Both groups were treated with phenylbutazone for 5 days. The CBD group received 0.03 mg/kg cannabidiol in hemp oil orally once daily for 14 days in addition to phenylbutazone treatment. All subjects were monitored for clinical parameters, oxidative status and blood counts. Pain and quality of life were also assessed using the Horse Chronic Pain Scale (HCPS). The CBD group showed a significant reduction in heart rate, respiratory rate, white blood cell count and oxidative stress (malondialdehyde lipid peroxidation). A significant reduction in HCPS scores was seen in both groups. Lower scores were recorded in the CBD group (3 med; range: 2/4) than in the C group (7 med; range: 4/10). The addition of a cannabidiol-based product to an analgesic protocol was well tolerated and showed positive effects on the treated subjects, improving their quality of life and pain relief.